Plan de negocios para la creación de una planta de procesamiento de conservas de aji “Santa Teresa” en la ciudad de Loja en el año 2015 - Loaiza Andrade, Félix Santiago (2015)
This study has as the main objective to develop a business plan to create the the processing plant of canned chili "Santa Teresita" in the city of Loja, as a tool which will allow to implement the business and make decisions in an efficient way, creating job opportunities for the development of the primary economic sector of the parish Chantaco. The methodology applied in the study, based on bibliographic research about market studies, identifying the techniques for design and its application in organizations, specifically in production businesses, allowed to characterize the producers of chili in the parish Chantaco in Loja, and therefore, determine the offer of raw materials. On the other hand, surveys applied to consumers, allowed to know the demand for this product based on likes and preferences, the competition, substitutes and and complements of chili, with with the profile of the consumers is defined, the actual demand and competition, also the unsatisfied demand, which is basic information to plan the production. Also this activity allowed to define costs and to calculate the income and profits, to make a technical and legal study, and generate information of financial feasibility of the business, coming to the conclusion that it is profitable, as it will show in the different chapters of the study, which content is summarized next: In the first chapter are characterized the producers of chili pepper from the organization of growers in Chantaco, and the characteristics of the area, the producers, and requirement of the grow are also described. In the second chapter there is the market study, where is defined the product, its uses, and applications, the users, and the market research; marking the potential, actual and effective demand, the offer and unsatisfied demand. In the third chapter the technical study is defined, determining the macro and micro localization, the flow of processes and distribution of the plant framed under the current legal environment, and the requirement of the plant and equipment. In the fourth chapter, through the legal study, it is described the process to create and legalize the chili production plant and the legal forms, concluding with the analysis of costs, incomes, profits, cash flow, equilibrium point and financial indicators, which demonstrates the feasibility of the business through the proposed plan.